ANALYSIS OF THE DYNAMICS OF COASTAL LANDFORM CHANGE BASED ON THE INTEGRATION OF REMOTE SENSING AND GIS TECHNIQUES: IMPLICATIONS FOR TIDAL FLOODING IMPACT IN PEKALONGAN, CENTRAL JAVA, INDONESIA - Yulianto, Fajar; Suwarsono, Suwarsono; Maulana, Taufik; Khomarudin, Muhammad Rokhis (Quaestiones Geographicae, 2019)
Coastal landforms are located in the interface zone between atmosphere, ocean and land surface systems formed by the geomorphic process of erosion, depositional, and subsidence. Studying the dynamics of coastal landform change is important for tracing the relationship between coastal landform changes and tidal flooding in the coastal areas of Pekalongan, Indonesia. The method of integrating remote sensing data with geographic information system (GIS) techniques has been widely used to monitor and analyze the dynamics of morphology change in coastal landform areas. The purpose of this study is to map the dynamics of landform change in the study area from 1978 to 2017 and to analyze its implications for the impact of tidal flooding. The results of the mapping and change analysis associated with coastal landforms can be classified into four landform types: beach, beach ridge, backswamp and alluvial plain. Changes in coastal morphology and landform topography affected by land subsidence and changes in land use/land cover have contributed to the occurrence of tidal flooding in the study area. Beach ridges perform an important role as natural levees which hold back and prevent the entry of seawater at high tide in coastal areas. A limitation of this study is that, as it focuses only on the physical aspects of coastal landform characteristics for one of the factors causing tidal flooding.